남북한 농수산 분야 경제협력사업 추진실태와 활성화 대책 - 권태진 (한국농촌경제연구원, 2008)
This study aims to figure out the problems of inter-Korean economic cooperation and suggests strategies for activating cooperation. To do so, the government's role is emphasized because there are more important things such as establishing related policies, system adjustment, and creation of cooperative foundation and circumstance. The relationship between south and north Korea has become closer and inter-Korean economic cooperation has progressed in both quantity and quality, since the 6?15 declaration. Inter-Korean economic cooperation in agriculture and fisheries sector had many difficulties in the early days but it has settled down since the mid-2000s. So far, 21 cooperation plans have been approved in agriculture and fisheries sector and among the 21 cooperation plans, four of them has been canceled and the rest of them is valid for now. South and north Korea have already agreed to cooperate in many agriculture and fisheries sector related businesses. In addition, they decided to do various business cooperations through the first meeting of the Inter-Korean Agricultural Cooperation Committee in 2005, and they have also agreed on their future cooperation at the 2007 Inter-Korean summit meeting. However, there have not been any progress so far and the future is unclear. The South and North announced four Agreements on the Inter-Korean Economic Cooperation as a way to stabilize the economic cooperation between the two. And it has become officially effective since August 2003. But there are no detailed guiding principles, so the performance of the agreements is very limited. To revitalize the economic cooperation, the contents of four Agreements on Inter-Korean Economic Cooperation should be more concrete. Also the economic environment of the North should change. Especially, the Investment Law for Foreigners, which is applied only to foreign countries, needs to be applied to the South equally. The relationship between two Koreas must be fundamentally stable and to do that, consistency of the policy is required. We should be ready to carry out any concrete plans in case the relationship between two Koreas improve. If private enterprises lead the economic cooperation, it would be accorded with the government policy, which has been mutually-beneficial and co-prosperous inter-Korean relationship. The business under unfavorable environment should be carried out supportively at first and move into an investment business or a contract production gradually. Supportive businesses, which are led by the central government or non-governmental organizations(NGOs), should have more interests in guiding the North. They will have to make the North turn its eyes to reform and open policy for the future. South Korea should set policies for the North in long-term perspective and it should be carried out consistently and continuously in order to revitalize the economic cooperation in agriculture and fisheries sector. The purpose of inter-Korean economic cooperation should be settled down for the fixed peace of Korean peninsula and the mutually-beneficial and co-prosperous inter-Korean relationship. There should be a system that is capable of checking up the original place of products because they are produced with materials from the North. The economic cooperation could be successful when the safety system is prepared. It is also important to make global environments. North Korea’s nuclear problem is related to inter-Korean cooperation very deeply, so the participants of six-party meeting will have to show their efforts for revitalizing the South and North economic cooperation. From now on, it is the priority for the North to join international financial institutions and become a member of international society for securing financial resources. Recently, South Korea’s government made a Fund for Development of North Korea at IBRD and it will be a good example to support the economic development of the North.